A Multi-Dimensional Resource Allocation Scheme: In Beam Hopping Technique Enhanced MF-TDMA Satellite Systems - Yifeng Jin; Zhong Zheng; Hanyu Zheng; Minglong Pu; Junjie Zeng; Zihe Gao (IEEE Access)
Against the backdrop of the widespread deployment of 5G systems and humanity’s entry into a new era of sixth-generation mobile communication, countries are now turning their attention to exploring uncharted territories through satellite communication. Multi-beam satellite communication enables the provision of services to ground user terminals via multiple spot beams, thereby increasing the power spectral density and achieving ground terminal miniaturization. While both MF-TDMA technology and beam hopping technology can significantly enhance the flexibility of multi-beam satellite communication systems, there are certain limitations associated with using either technology in isolation. In this study, we focus on the downlink transmission scenario for an MF-TDMA satellite system enhanced by beam hopping technology. We propose a joint optimization approach that encompasses subcarrier power allocation, subcarrier bandwidth allocation, beam hopping pattern selection, and subcarrier-user assignment to minimize the matching error between the satellite capacity and traffic demand of users with different priorities. To address this problem effectively, we present a two-stage optimization strategy. Simulation results demonstrate that our proposed two-stage resource allocation scheme outperforms other benchmark algorithms in minimizing the total priority-weighted matching error by at least 14% across various system settings.